The never war - MacHale, D. J. (New York Aladdin Paperbacks, 2003)
Bobby and the Traveler from Cloral--Spader--have flumed to New York City, 1937. Against a backdrop of gangsters, swing music, and the distant sound of a brewing war, the two must uncover the evil Saint Dane's newest plot.
10 up.
Keywords: Time travel -- Juvenile fiction; Fantasy; Adventure and adventurers -- Fiction; Time travel -- Fiction; New York (N.Y.) -- Juvenile fiction; New York (N.Y.) -- Fiction